Inferences on Turkish Education Policies in the Light of International Education Policy Studies following the Compulsory Education Reform - Betül Balkar; Rabia Öztuzcu; Şahabettin Akşab (Educational Considerations, 2019)
The purpose of this study was to evaluate the developments observed in the Turkish education policies in the light of international scientific studies on education policy following the 12 year compulsory education (4+4+4) reform that took place in 2012. Data for the study that was carried out as scoping review and intrinsic case study were acquired via document analysis. For this purpose, scientific studies published in the 9 international education policy journals and National Education Council Report and Development Plans encompassing the education policies of Turkey after the year 2012 were analyzed via content analysis. According to the results of the study; the subjects in education policy studies were generally in accordance with the issues that are in the focus of Turkish educational policies. The results of the study were discussed in the light of international education policy studies with inferences regarding Turkish education policies.
Keywords: Turkish education policies; compulsory education reform; international education policy studies